FOCUS GROUP DISCUSSION SEBAGAI METODE PENGENALAN SISTEM INFORMASI MANAJEMEN KKP BERBASIS WEB DI UNIVERSITAS ISLAM NEGERI MATARAM - Maimun; Bahtiar; Ibrahim; Jannah, Zuhrupatul (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
This community service activity aims to introduce and introduce the web-based Practical Work Lecture (KKP) management information system at the State Islamic University (UIN) Mataram through the Focus Group Discussion (FGD) method. The activity, which was carried out on September 5, 2024, involved UIN Mataram lecturers who were directly involved in KKP management. In this activity, participants were given an explanation of the benefits and purposes of using a web-based information system, and were involved in a direct simulation to operate the system. The evaluation results showed a positive response from participants to the development of the system, with most feeling satisfied and ready to implement this system in KKP management. Through this activity, it is hoped that the KKP management information system can simplify and accelerate the KKP administration process at UIN Mataram, as well as support digital transformation in the academic environment.